Results of liver transplantation in patients with acute liver failure due to Amanita phalloides and paracetamol (acetaminophen) intoxication - Krasnodębski, Maciej; Grąt, Michał; Hołówko, Wacław; Masior, Łukasz; Wronka, Karolina M.; Grąt, Karolina; Stypułkowski, Jan; Patkowski, Waldemar; Krawczyk, Marek (Gastroenterology Review/Przegląd Gastroenterologiczny, 2016)
Introduction: Amanita phalloides and paracetamol intoxications are responsible for the majority of acute liver failures. Aim: To assess survival outcomes and to analyse risk factors affecting survival in the studied group. Material and methods : Of 1369 liver transplantations performed in the Department of General, Transplant, and Liver Surgery, Medical University of Warsaw before December 2013, 20 (1.46%) patients with Amanita phalloides (n = 13, 0.95%) and paracetamol (n = 7, 0.51%) intoxication were selected for this retrospective study. Overall and graft survival at 5 years were set as primary outcome measures. Results : Five-year overall survival after liver transplantation in the studied group was 53.57% and 53.85% in patients with paracetamol and Amanita phalloides poisoning, respectively (p = 0.816). Five-year graft survival was 26.79% for patients with paracetamol and 38.46% with Amanita phalloides intoxication (p = 0.737). Risk factors affecting patient survival were: pre-transplant bilirubin concentration (p = 0.023) and higher number of red blood cells (p = 0.013) and fresh frozen plasma (p = 0.004) transfused intraoperatively. Likewise, higher number of red blood cells (p = 0.012) and fresh frozen plasma (p = 0.007) transfused were risk factors affecting 5-year graft survival. Surprisingly, donor and recipient blood type incompatibility was neither the risk factor for 5-year overall survival (p = 0.939) nor the risk factor for 5-year graft survival (p = 0.189). Conclusions : In selected intoxicated patients urgent liver transplantation is the only successful modality of treatment. Risk factors affecting survival are in correspondence with the patient’s pre-transplant status (bilirubin level in serum) and intraoperative status (number of red blood cells and fresh frozen plasma transfused).